Comparison of virtual microscopy and glass slide microscopy among dermatology residents during a simulated in‐training examination. (29th June 2013) - Brick, Katherine E.; Sluzevich, Jason C.; Cappel, Mark A.; DiCaudo, David J.; Comfere, Nneka I.; Wieland, Carilyn N.
Abstract Background Virtual microscopy is increasingly being used in dermatopathology educational settings. Objective The objective is to evaluate diagnostic accuracy and attitudes between virtual microscopy and traditional glass slide microscopy among dermatology residents. Methods A 48‐question dermatopathology examination was administered to 35 dermatology residents at three different dermatology residency training sites during the 2011–2012 academic year with half (n = 24) of the questions using the gold standard of glass slide microscopy and half (n = 24) using whole, scanned virtual slides. Correct number of questions using glass slides and virtual slides was evaluated. Participants were surveyed regarding previous experience with digital slide imaging; quality, ease of use, and speed of slide review; and overall microscopy preferences. Results Overall, diagnostic accuracy was better with glass slides than virtual slides (p = 0.01). However, no statistically significant difference was found in diagnostic accuracy of first‐year trainees (p > 0.99) or trainees with exposure to virtual microscopy greater than two times per month (p = 0.27). There was no overall personal preference for glass slide vs. virtual microscopy. Limitations Different cases and questions were used for glass slides and virtual microscopy. Conclusions Diagnostic accuracy with virtual microscopy is dependent on year of residency training and prior experience with virtual microscopy.